Persuasive Communication Strategy of Village Midwives in Reducing Community Stunting Rate in Posyandu (Gunung Baringin Village) - Paisah Nur Nasution*; Muhammad Al Fikri (Universitas Syiah Kuala, 2023)
This study aims to find out how persuasive communication strategies by village midwives can reduce stunting in the posyandu (Gunung Meriah Baringin Village). The type of research used in this research is qualitative research with a descriptive approach which aims to describe the efforts made by the posyandu to influence the community in reducing stunting rates in the Baringin Village. Based on the results of research that has been done, it is known that village midwives' persuasive communication strategies in reducing stunting rates in the community are divided into several programs, including: determining the objects and objectives of recipients of information, conducting persuasive techniques, and building educational communication.